Pharmacoeconomic analysis of drug supply of the military personnel with chronic bronchitis - O. V. Plieshkova; O. V. Bielozorova; M. V. Bilous; D. V. Drozdov; A. V. Nikituk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
Despite the superiority of bronchitis in the structure of respiratory diseases in the military personnel, its course develops with certain peculiarities due to the peculiarities of military service. Consequently, the optimization of the costs of providing the military personnel with medicines is becoming more and more of medical and social importance. Reasonable selection of medicines in the treatment of chronic bronchitis is the result of the choice of effective and safe drugs, considering the cost of the components for military health care.